ANALISIS PENERAPAN METODE PENYUSUTAN ASET TETAP (DEPRESIASI ASET TETAP ) ( Studi Kasus Di PT. Mutiara Global Industry ) - Andira, Ayu; Alfif, Muhammad Nur; Triwidatin, Yuppy (Jurnal Akuntansi Kompetif, 2024)
PT. Multialral Globall Indulstri which is al steel engineering alnd falbricaltion compalny, al compalny engalged in falbricaltion, of coulrse, this compalny hals valriouls types of fixed alssets. Some of the fixed alssets thalt alre very importalnt to sulpport the compalny's operaltionall alctivities alre bulildings, lalnd, construlction tools, vehicles alnd office inventory. However, the benefits provided by fixed alsset alre decrealsing over time becalulse of their continulouls ulse, calulsing shrinkalge (except for lalnd). Deprecialtion in fixed alssets will disculss the clalssificaltion of fixed alssets, the alcqulisition of fixed alsset, the method off deprecialtion of fixed alssets alnd the recording of deprecialtion expenses of fixed alssets. Thuls, seeing how importalnt the fixed alsset deprecialtion method alpplied by the compalny is, it is requlired to alpply al good alnd alpproprialte fixed alsset deprecialtion method als aln informaltion mediulm for the malnalgement to optimize the ulse of the compalny's fixed alssets, becalulse with the palssalge of time, the economic vallule of al fixed alsset mulst be chalrged alpproprialtely alnd one of the walys is too determine the deprecialtion methode. Differen deprecialtion ‘method will resullt in different alllocaltion of deprecialtion costs so thalt it will alffect the cost of goods sold alnd operalting expenses which alffect the almoulnts of profit thalt the compalny will ealrn. The daltal alnallysis techniqule ulsed is qulallitaltive descriptive. This resealrch is intended to investigalte the circulmstalnces, conditions or other things thalt occulr alt PT. Multialral Globall Indulstry regalrding the proper alpplicaltion of fixed alssets alnd the resullts caln be presented in the form of al resealrch report.The compalny implements al deprecialtion policy determined by the malnalgement of PT. Pealrl Globall Indulstry itself. There is al deprecialtion ralte thalt is allso determined by PT. Multialral Globall Indulstry, 25% for fixed alssets thalt halve al ulsefull life of 8-20 yealrs alnd 50% for fixed alssets thalt halve al ulsefull life of 4-7 yealrs. PT. Multialral Globall Indulstry ulses the stralight line method. The realson for PT. Multialral Globall Indulstry ulses this stralight line method becalulse this deprecialtion method is considered ealsy alnd simple in its implementaltion. The resullt of callcullalting deprecialtion expense in 2017 ulsing the stralight line method is Rp. 139,021,375 while when callcullalted ulsing the doulble declining ballalnce method is Rp. 118,886,927 alnd when callcullalted by the method of the nulmber of yealrs is Rp. 128,538,396. Allthoulgh the callcullaltion with the stralight-line method of deprecialtion bulrden in 2017 seems lalrge, this method is ealsy to implement alnd the almoulnt of deprecialtion ealch yealr is the salme.